Emergence delirium in children undergoing dental surgery under general anesthesia. Issue 9 (25th June 2020) - Jooma, Zainub; Perrie, Helen; Scribante, Juan; Kleyenstuber, Thomas
Abstract: Background: Emergence delirium is a well‐described complication in pediatric anesthesia, occurring more often following short surgical procedures using volatile anesthetics with a rapid recovery profile. Dental extractions and conservation dentistry are commonly performed in children and are not painful postoperatively. The use of nerve blocks and local anesthetic infiltration intraoperatively limits nociception and obviates the need for opioids, allowing for more objective assessment of emergence delirium. Aim: The purpose of this preliminary study was to describe the incidence of emergence delirium and the associated risk factors in children undergoing elective dental surgery under general anesthesia at a regional academic hospital in South Africa. Methods: A prospective, descriptive study of healthy children aged 2‐6 years was undertaken. Patients were anesthetized using standardized protocols. Assessments included demographics of the child and caregiver, child anxiety at induction using the modified Yale Preoperative Anxiety Scale, intraoperative events, and Paediatric Anaesthesia Emergence Delirium score in the recovery room. Data were assessed for associations and correlations. Results: Ninety‐one children with a mean age of 3.9 (SD = 0.9) years were included. Anxiety was present in 69.2% at induction and emergence delirium occurred in 51.6% of the patients. The mean (SD, range) Paediatric Anaesthesia Emergence Delirium score in the patients without emergence delirium was 7 (2.65, 0‐9) and in patients with emergence delirium was 14 (2.52, 10‐18). Children with emergence delirium required more interventions in the recovery room but few required pharmacological treatment. Conclusions: Emergence delirium occurs commonly after dental surgery, and the majority of the children presenting for dental surgery are anxious at induction. Children with emergence delirium require more interventions in the recovery room but few require pharmacological treatment.